2021
DOI: 10.1016/j.annonc.2021.08.328
|View full text |Cite
|
Sign up to set email alerts
|

49P A phase II trial of nivolumab and gemcitabine and S-1 as the first-line treatment in patients with advanced biliary tract cancer

Abstract: Background: The regimen of modified gemcitabine and S-1 (GS) is active and safe for patients with advanced biliary tract cancer (ABTC) in our previous study. Herein, we report the results of a single arm phase II of Nivolumab plus modified GS as the firstline treatment in ABTC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…PD-1 inhibitors, which are important components of ICIs, are increasingly used in BTC therapy [ 8 , 24 , 25 ]. Nivolumab combined with gemcitabine and tegafur chemotherapy has shown a good therapeutic effect in the first-line treatment of advanced BTC, with an ORR of 41.7% [ 24 ]. A study of PD-1 inhibitors plus lenvatinib for unresectable BTC showed an ORR of 42.1% [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…PD-1 inhibitors, which are important components of ICIs, are increasingly used in BTC therapy [ 8 , 24 , 25 ]. Nivolumab combined with gemcitabine and tegafur chemotherapy has shown a good therapeutic effect in the first-line treatment of advanced BTC, with an ORR of 41.7% [ 24 ]. A study of PD-1 inhibitors plus lenvatinib for unresectable BTC showed an ORR of 42.1% [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…4d and 4e, left panel). We changed systemic therapy to nivolumab plus modi ed gemcitabine and TS-1 (NGS) every 2 weeks [13]. After NGS treatment for 3 months, the multiple metastatic lymphadenopathies obviously decreased bilateral pleural effusion improved which lasted for almost one year (Fig.…”
Section: Response Of Ebv-lelcc To Anti-pd-1 Monoclonal Antibody Treat...mentioning
confidence: 99%
“…. They may represent news options but need further studies (17,18). However, the NuTide:121 trial comparing cisplatin-NUC-1031, an optimized gemcitabine derivative, with CISGEM (19) was stopped prematurely in January 2022 by the study's independent data monitoring committee due to futility at interim analysis with no published results to date, despite promising results in phase 1 (20).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%